A cross-lagged model of the link between parental psychological control and adolescent aggression. (July 2019) - He, Yan; Yuan, Keman; Sun, Liping; Bian, Yufang
Abstract: Introduction: The present study investigated the longitudinal relationship between parental psychological control and adolescent aggression in Chinese adolescents. We also explored whether adolescent gender plays a moderating role in this relationship. Methods: A total of 2458 adolescents (mean age = 13.20 ± 0.65 years; 51.3% male) from Beijing, China, participated at three time points during middle school, 1 year apart. Parental psychological control, adolescent aggression, and demographic characteristics were self-reported at each time point. A cross-lagged model was conducted. Results & conclusions: The results showed that adolescent aggression at Time 1 positively predicted parental psychological control at Time 2. Parental psychological control at Time 2 positively predicted adolescent aggression at Time 3. Adolescent aggression at Time 2 predicted parental psychological control at Time 3. These findings provide evidence that supports the reciprocal effects model and further our understanding of the longitudinal and bidirectional relationship between parental psychological control and adolescent aggression. No significant adolescent gender differences were found in terms of the reciprocal effect model.